The influence of profitability, liquidity, leverage, and company growth on corporate social responsibility disclosure - Sinta Dwi Febriyanti; Wida Purwidianti; Hengky Widhiandono; Alfalisyado Alfalisyado (Institute of Computer Science (IOCS), 2023)
The influence of profitability (X1), liquidity (X2), leverage (X3), and company growth (X4) on Corporate Social Responsibility Disclosure (Y) is the aim of this research. This study uses a quantitative approach. This research involved 118 non-cyclical consumer companies on the Indonesia Stock Exchange in 2020–2022. The number of samples is 34 companies, and the total data is 102. The research results show that the variables leverage (X3) and company growth (X4) influence the Disclosure of Corporate Social Obligations (Y). On the other hand, the profitability (X1) and liquidity (X2) variables do not affect the Corporate Social Responsibility Disclosure (X4). The influence of variable X on Y is 7.1%, seen from the Adjusted R2 value, while other variables influence the rest